High Reliability and Fast-Speed Phase-Change Memory Based on Sb70Se30/SiO2 Multilayer Thin Films - Dan Zhang; Yifeng Hu; Haipeng You; Xiaoqin Zhu; Yuemei Sun; Hua Zou; Yan Zheng (Advances in Materials Science and Engineering)
Sb70Se30/SiO2 multilayer thin films were applied to improve the thermal stability by RF magnetron sputtering on SiO2/Si (100) substrates. The characteristics of Sb70Se30/SiO2 multilayer thin films were investigated in terms of crystallization temperature, ten years of data retention, and energy bandgap. It is observed that the crystallization temperature, 10-year data retention, and resistance of Sb70Se30/SiO2 multilayer composite thin films exhibited a higher value, suggesting that Sb70Se30/SiO2 multilayer composite thin films have superior thermal stability. The AFM measurement suggests that the SbSe (1 nm)/SiO (9 nm) multilayer thin films possess a smaller surface roughness (RMS = 0.23 nm). Besides, it was found that the phase-change time of SbSe (1 nm)/SiO (9 nm) multilayer thin films was shorter than that of GST in the process of crystallization and amorphization.